Perceptual Difficulty Persistently Increases Dominance in Binocular Rivalry—Even Without a Task. (April 2021) - Einhäuser, Wolfgang; Sandrock, Annalena; Schütz, Alexander C.
A major objective of perception is the reduction of uncertainty about the outside world. Eye-movement research has demonstrated that attention and oculomotor control can subserve the function of decreasing uncertainty in vision. Here, we ask whether a similar effect exists for awareness in binocular rivalry, when two distinct stimuli presented to the two eyes compete for awareness. We tested whether this competition can be biased by uncertainty about the stimuli and their relevance for a perceptual task. Specifically, we have stimuli that are perceptually difficult (i.e., carry high perceptual uncertainty) compete with stimuli that are perceptually easy (low perceptual uncertainty). Using a no-report paradigm and reading the dominant stimulus continuously from the observers' eye movements, we find that the perceptually difficult stimulus becomes more dominant than the easy stimulus. This difference is enhanced by the stimuli's relevance for the task. In trials with task, the difference in dominance emerges quickly, peaks before the response, and then persists throughout the trial (further 10 s). However, the difference is already present in blocks before task instruction and still observable when the stimuli have ceased to be task relevant. This shows that perceptual uncertainty persistently increases perceptual dominance, and this is magnified by task relevance.